Diagnostic work‐up for severe aplastic anemia in children: Consensus of the North American Pediatric Aplastic Anemia Consortium. Issue 11 (20th August 2021) - Shimano, Kristin A.; Narla, Anupama; Rose, Melissa J.; Gloude, Nicholas J.; Allen, Steven W.; Bergstrom, Katie; Broglie, Larisa; Carella, Beth A.; Castillo, Paul; de Jong, Jill L. O.; Dror, Yigal; Geddis, Amy E.; et al.
Abstract: The North American Pediatric Aplastic Anemia Consortium (NAPAAC) is a group of pediatric hematologist‐oncologists, hematopathologists, and bone marrow transplant physicians from 46 institutions in North America with interest and expertise in aplastic anemia, inherited bone marrow failure syndromes, and myelodysplastic syndromes. The NAPAAC Bone Marrow Failure Diagnosis and Care Guidelines Working Group was established with the charge of harmonizing the approach to the diagnostic workup of aplastic anemia in an effort to standardize best practices in the field. This document outlines the rationale for initial evaluations in pediatric patients presenting with signs and symptoms concerning for severe aplastic anemia.